Post retention strength of apical and conventional coating obturation methods using bioceramic sealer: a laboratory investigation - Benjarat Chanapairin; Sirinya Kulvitit; Chankhrit Sathorn (BMC, 2024)
Abstract Background Once bioceramic sealer (BCS) enters the dentinal tubules, it cannot be reliably removed. BCS-occupied dentinal tubules reduce fibre post retention strength. Coating gutta-percha with BCS only on the apical portion may improve post retention strength due to increased retention strength between the dentin and resin cement interface. The aim of the study was to test this hypothesis. Methods Root canals of 27 extracted human mandibular premolars were instrumented and randomly assigned to three obturation methods: conventional coating (CC), non-coating (NC), and apical coating (AC). The root canals were obturated with gutta-percha to 4 mm from the working length under an operating microscope. After the BCS was completely set, post spaces were prepared, and quartz fibre posts were cemented. The apical 4.5 mm of the roots were removed. Two samples were prepared at the apical, middle, and coronal root levels (one for scanning electron microscope (SEM) study and another for the push out bond strength (PBS) test). After the PBS test, the samples were examined with a stereo microscope to determine the failure mode: dentine-cement (DC), post-cement (PC) and mixed. The PBS data were analysed by One way ANOVA for the specific obturation method effects. Repeated ANOVA was used for the specific effects of the root levels on PBS in different obturation methods. Results At all three root levels, more continuous hybrid layers and denser resin tags were found in the NC and AC than the CC group. The AC and NC groups' PBS was significantly higher than the CC group at the apical 1/3 (p = 0.002 and p = 0.001) and coronal 1/3 (p = 0.016 and p = 0.041). The PBS in the CC group at the middle 1/3 was significantly higher than the apical 1/3 (p = 0.022). DC failure mode was most commonly found in the CC group, while PC failure mode was found most frequently in the NC and AC groups. Conclusions The apical coating obturation method significantly increased PBS over the conventional coating method, potentially reducing fiber post dislodgement. However, this study was only preliminary. Clinical studies are required to confirm the results.